Determinants Influencing Surgical Outcomes in Chronic Osteomyelitis: A Clinical Evaluation - Dr. Girish Rao Suryakari; Dr.M.MD Saqlain; Dr.Bekkem Mani Dinakar Reddy; Dr.Arumalla Karteek; Dr.Nagakiran K.V; Dr.Shaik Saddam Hussain, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chronic osteomyelitis is a persistent infection of bone and bone marrow which results from trauma, surgery, or hematogenous spread. The condition is complicated by microbial biofilm formation, host immune evasion, and the presence of implants. It poses a significant clinical challenge due to high recurrence rates and difficulties in eradication. Objective: To evaluate the risk factors associated with chronic osteomyelitis, assess surgical outcomes, and determine the influence of these risk factors on patient recovery. Methodology: This prospective observational study was conducted at PES Institute of Medical Sciences and Research, Kuppam, from June 2023 to June 2024. Thirty-four patients diagnosed with chronic osteomyelitis of long bones were included. Data were collected on demographic characteristics, comorbidities, injury and implant history, microbiological findings, and laboratory parameters. Functional outcomes were assessed using LEFS and DASH scores at 1-, 2-, and 3-month follow-ups. Statistical analysis was performed using SPSS v26 with ANOVA and chi-square tests. Results: The majority of participants were males (85.3%) aged 40–60 years. Most cases were associated with the presence of implants (94.1%), particularly nails and plates. Common risk factors included diabetes mellitus and smoking. Among microbiological isolates, Staphylococcus aureus, E. coli, and coagulase-negative staphylococci were predominant. Significant associations were found between functional outcomes and factors such as age, duration of symptoms, implant status, hemoglobin levels, and Cierny-Mader classification. Conclusion: Implant-related infections and host factors such as anemia, diabetes, and smoking significantly influence the development and outcome of chronic osteomyelitis. Early identification and aggressive surgical management combined with targeted antibiotic therapy are essential for favorable recovery.